2021
DOI: 10.1177/13623613211050440
|View full text |Cite
|
Sign up to set email alerts
|

Influences of student race/ethnicity and gender on autism special education classification considerations

Abstract: Although the prevalence of autism continues to rise, identification disparities across race/ethnicity and gender persist in schools. The under- and overidentification of specific populations receiving special education services under the classification of autism contribute to misappropriation or lack of intervention services for students. Practicing school psychologists ( N = 229) reviewed one of eight vignettes depicting a student displaying possible autism symptoms that varied only by student race/ethnicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…White British children who were not ‘school ready’ had higher odds of being identified as having SEN relative to ethnic minority peers who were not ‘school ready’. This is in line with previous research which has found ethnic biases in smaller samples 20–22. More broadly, this adds to a growing body of literature indicating that individuals from ethnic minority backgrounds are identified later than their ethnic majority counterparts in conditions as diverse as autism,28 tuberculosis29 and cancer 30.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…White British children who were not ‘school ready’ had higher odds of being identified as having SEN relative to ethnic minority peers who were not ‘school ready’. This is in line with previous research which has found ethnic biases in smaller samples 20–22. More broadly, this adds to a growing body of literature indicating that individuals from ethnic minority backgrounds are identified later than their ethnic majority counterparts in conditions as diverse as autism,28 tuberculosis29 and cancer 30.…”
Section: Discussionsupporting
confidence: 90%
“…19 Conversely, research has shown that children from ethnic minority backgrounds are less likely to have SEN, but this may reflect structural inequalities in identification. [20][21][22] These structural inequalities may arise due to variation in views relating to child development between cultures 23 or knowledge of and access to services and support within ethnic minority families. 20 To date, no existing research has investigated whether such ethnic differences vary as a function of school readiness.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, both complex and single probiotics were used in the studies we included, some probiotics consist of a variety of bene cial bacteria, while others have only a single strain, such as PS128. Fourthly, all RCTs were published in different countries, the researches were scattered in Asia, Europe and the United States, race and ethnicity maybe important in uencing factors of autism (34). Higher quality and larger sample size clinical studies are needed for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the results obtained showed a good fit and reliability, which positions it as an excellent instrument for future researchers and professionals in the field of education to assess the social skills of young people in primary education in diverse contexts. In today's social context, having good social skills is especially necessary (Golson et al, 2022). Teaching schools should encourage the use and practice of social skills, both in terms of teaching practices and mutual social interactions among prospective teachers (Pan and Hung, 2022).…”
Section: Discussionmentioning
confidence: 99%